Synthesis, Molecular Modelling and In Vitro Anti‐inflammatory Activity of Novel 1, 2, 4‐Triazolo[4, 3‐a]quinoxaline Derivatives. Issue 26 (8th July 2022) - Doğan, Inci Selin; Kahveci, Bahittin; Sari, Suat; Kolci, Kübra; Reis, Rengin; SIPAHI, Hande
Abstract: In this study, a series of 12 new 1, 2, 4‐triazolo[4, 3‐a]quinoxalines (3 a ‐l ) were synthesized to investigate their anti‐inflammatory activities. An efficient method for synthesis of 1, 2, 4‐triazolo[4, 3‐a]quinoxaline compounds (3 a ‐l ) rendered a cyclo‐condensation between iminoester derivatives (Compounds 1 a ‐l ) and 1‐(quinoxalin‐2‐yl)hydrazine (Compound 2 ). The synthesized compound's structural elucidation was carried out using 1 H‐ and 13 C‐NMR, Mass analysis. Cytotoxicity profiles of the title compounds were assessed by MTT assay, and anti‐inflammatory activities were investigated by determining nitrite levels in LPS‐induced RAW264.7 murine macrophage cells. In addition, the ability of the compounds to reduce nitrite levels was modelled using molecular docking method. Compound 3 a ‐l showed good anti‐inflammatory activities. Compound 3 f exhibited the most remarkable nitrite‐reducing effect (65.12±1.62 %), which was similar to the nitrite inhibition seen with IND (63.83±4.20 %) compared to LPS‐induced control. Besides, 3 f was followed by 3 i and 3 g, causing a significant decline in nitrite levels (51.56±8.68 % and 51.13±8.29 %, respectively). Molecular docking studies predicted that the compounds showed high affinity and formed key interactions with the active site of inducible nitric oxide synthase (iNOS), a key enzyme responsible for elevated nitrite levels. Thus, the current study explored a new series of 1, 2, 4‐triazolo[4, 3‐a]quinoxaline analogs with promising nitrite‐reducing effects, most probably due to iNOS inhibition. Abstract : In this study, we have synthesized 12 new 1, 2, 4‐triazolo[4, 3‐a]quinoxaline derivative compounds (3 a ‐l) via conventional methods. Antiinflammatory activities of these compounds were done in vitro . The compound's cytotoxicity profiles were assessed by MTT assay and antiinflammatory activities were investigated via nitrite level in LPS‐induced RAW264.7 murine macrophage cells. Molecular docking was performed to predict iNOS inhibition of the title compounds. The derivative carrying the m‐ chlorobenzyl (compound 3 f ) substituent was found to be the most active, followed by the compounds carrying the m‐ bromobenzyl (3 i ) and o ‐chlorobenzyl (3 g ) substituent. The result was supported by molecular modeling.